148k views
3 votes
Cumpute:

11squared-(12-4)squared + 3 =

User Shabeer K
by
5.7k points

1 Answer

7 votes

Answer:

The result is 60

Explanation:

We have to use this expression showing BODMAS rule. According to the rule, we must first solve the brackets. In our expression, the term within the bracket is (12-4) squared = (8) squared = 64.

Then we need to perform the addition followed by subtraction.

The expression becomes:

11 squared - 64 + 3

= 121 - 64 + 3

= 124 - 64

= 60

So, the result of the expression is 60.

User Anam Ansari
by
5.7k points